PENGGUNAAN MEDIA WORDWALL PADA MATA PELAJARAN SOSIOLOGI UNTUK MENCIPTAKAN SUASANA BELAJAR YANG MENYENANGKAN DI KELAS - Nada Shafa Aulia; Raja Azura; Imam Malik; Baiq Sugini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
A pleasant learning atmosphere is an important factor in supporting the achievement of optimal learning objectives. One interactive medium that can create a pleasant learning atmosphere is Wordwall. Therefore, the purpose of this study is to determine how the learning atmosphere in the classroom is affected by the use of Wordwall in Sociology lessons, as well as to fulfill the requirements of the Teaching Assistance (AM) program and the Real Work Lecture (KKN) program. This study used a qualitative method with a descriptive approach. The study was conducted at SMAN 1 Narmada with the research subjects being 10th grade students who took Sociology classes. Data collection techniques included observation, interviews, and documentation. The research instruments used were observation guidelines and interview guidelines to observe and explore student involvement and participation during the learning process. The results of the study indicate that the use of Wordwall media is able to create a learning atmosphere for students, which is characterized by the growth of student activity in asking questions, answering questions, expressing opinions, and involvement in class discussions. Thus, the use of Wordwall media as interactive learning media has been proven to create a pleasant learning atmosphere in Sociology lessons.